Toll-like receptor ligands induce expression of the costimulatory molecule CD155 on antigen-presenting cells. - Neha Kamran; Yoshimi Takai; Jun Miyoshi; Subhra K Biswas; Justin S B Wong; Stephan Gasser (PLoS ONE, 2013)
Genotoxic stress and RAS induce the expression of CD155, a ligand for the immune receptors DNAM-1, CD96 and TIGIT. Here we show that antigen-presenting cells upregulate CD155 expression in response to Toll-like receptor activation. Induction of CD155 by Toll-like receptors depended on MYD88, TRIF and NF-κB. In addition, IRF3, but not IRF7, modulated CD155 upregulation in response to TLR3 signals. Immunization of CD155-deficient mice with OVA and the TLR9 agonist CpG resulted in increased OVA-specific IgG2a/c titers when compared to wild type mice. Splenocytes of immunized CD155-deficient mice secreted lower levels of IL-4 and fewer IL-4 and GATA-3 expressing CD4(+) T cells were present in the spleen of Cd155(-/-) mice. Our data suggest that CD155 regulates T(h)2 differentiation. Targeting of CD155 in immunization protocols using peptides may represent a promising new approach to boost protective humoral immunity in viral vaccines.